Penggunaan calcium alginate dressing terhadap penyembuhan luka dm: Case report - Suprapti, Tuti; Muslim, Dede Nur Aziz; Anri, Anri (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2024)
Background: The use of calcium alginate dressing in the wound healing process in diabetes mellitus (DM) plays an important role as a wound dressing material that can help speed up the healing process. Calcium alginate functions to absorb exudate from wounds, create a moist environment that supports tissue regeneration, and prevents infection. This material is also able to stimulate the hemostasis process and reduce swelling, which is very beneficial for DM sufferers who often experience problems healing wounds due to disorders of blood circulation and the immune system. Purpose: To find out the healing process in DM wounds with the wound care method using Calcium Alginate Dressing with the aim of speeding up the wound healing process in DM Patients. Method: Pre-experiment method without control one group pre-test post-test design. The population of this study were DM patients with diabetic wounds and samples were taken using purposive sampling so that the total sample was 3 people. The research instrument used was the Bates-Jensen wound assessment tool (BWAT) with assessment criteria for a minimum BWAT severity score of 13-20, BWAT mild severity score of 21-30, BWAT moderate severity score of 31-40, BWAT Critical severity score of 41-60. The data analysis used in this research is descriptive analysis. Results: There was a change in the acceleration of the wound healing process from a critical severity score of 41-50 to a moderate severity score. The principle of wound care by creating a moist wound healing environment or keeping the wound environment always moist (not wet or dry) is in line with the modern principle of moisture balance dressing, namely selecting the type of dressing with a moist method to increase fibrinolysis, reduce infection, stimulate the formation of active cells and angiogenesis. Conclusion: There are significant changes in the wound healing process in DM patients.Suggestion: Further research is still needed to explore the optimal duration of calcium alginate use and further evaluate its effectiveness in various types of diabetic wounds. Keywords: Calcium Alginate; DM Patient; Wound Healing Process Pendahuluan: Penggunaan kalsium alginat Dressing dalam proses penyembuhan luka pada diabetes melitus (DM) berperan penting sebagai bahan pembalut luka yang dapat membantu mempercepat proses penyembuhan. Kalsium alginat berfungsi untuk menyerap eksudat dari luka, menciptakan lingkungan lembap yang mendukung regenerasi jaringan, serta mencegah infeksi. Material ini juga mampu merangsang proses hemostasis dan mengurangi pembengkakan, yang sangat bermanfaat bagi penderita DM yang sering mengalami masalah dalam penyembuhan luka akibat gangguan peredaran darah dan sistem imun. Tujuan: Untuk mengetahui proses penyembuhan pada luka DM dengan metode perawatan luka menggunakan balutan Calcium Alginate Dressing dengan tujuan untuk mempercepat proses penyembuhan Luka Pada Pasien DM. Metode: Metode pre-eksperimen tanpa control one group pre-test post-test design. Populasi penelitian ini adalah pasien DM dengan luka diabetik dan pengambilan sampel menggunakan purposive sampling sehingga jumlah sampel sebanyak 3 orang. Instrumen penelitian yang digunakan adalah alat penilaian luka bates-jensen (BWAT) dengan kriteria penilaian skor keparahan minimal BWAT 13-20, skor keparahan ringan BWAT 21-30, skor keparahan sedang l BWAT 31-40, skor keparahan Kritis BWAT 41- 60. Analisa data yang digunakan dalam penelitian ini adalah Analisa Deskriptif. Hasil: Adanya perubahan percepatan proses penyembuhan luka dari skor keparahan kritis 41-50 menjadi skor keparahan sedang. Prinsip perawatan luka dengan menciptakan lingkungan moist wound healing atau menjaga supaya lingkungan luka selalu dalam keadaan lembab (tidak basah atau kering) sejalan dengan prinsip modern dressing moisture balance yaitu pemilihan jenis balutan (dressing) dengan metode moist untuk meningkatkan fibrinolisis, mengurangi infeksi, menstimulasi pembentukan sel aktif dan angiogenesis. Simpulan: Ada perubahan yang signifikan dalam proses penyembuhan luka pada pasien DM. Saran: Penelitian lebih lanjut masih diperlukan untuk mengeksplorasi durasi optimal penggunaan kalsium alginat dan evaluasi lebih lanjut terhadap efektivitasnya pada berbagai jenis luka diabetik. Kata Kunci: Calcium Alginate; Pasien DM; Proses Penyembuhan Luka